Cold acclimation has a differential effect on leaf vascular bundle structure and carbon export rates in natural Arabidopsis accessions originating from southern and northern Europe - Katja Schneider (Plant Direct, 2020)
Abstract Acclimation to low but non‐freezing temperature represents an ecologically important process for Arabidopsis thaliana but also for many other plant species from temperate regions. Cold acclimation comprises and affects numerous molecular and physiological processes and the maintenance of sugar supply of sink tissue by photosynthetically active source tissue is essential for plant survival. Here, changes in vascular bundle (VB) structure at the leaf petiole were analysed together with sucrose exudation rates before and after cold acclimation. Six natural Arabidopsis accessions originating from southern and northern Europe were compared. Photosynthetic efficiency, that is, maximum and effective quantum yield of photosystem II, revealed a significant effect of environmental condition. Only for northern accessions was a highly significant negative correlation observed between leaf sucrose exudation rates, xylem, and petiole cross‐sectional areas. Furthermore, only for northern accessions was a significant increase of VB and leaf petiole cross‐sectional area observed during cold acclimation. In contrast, variance of cross‐sectional areas of cold acclimated southern accessions was strongly reduced compared to control plants, while mean areas remained similar under both conditions. In summary, these findings suggest that natural Arabidopsis accessions from northern Europe significantly adjust sink strength and leaf VB structure to maintain plant growth and photosynthesis under low temperature.